(3CSdhH GdMhGQ aj GdMOjK GdfHhj (B:s (3OQGSI HdGZjI (B/s - (3CjhH, Ndjd eMeOs ((3OeTb (B:s (3OGQ GdfhGOQ,s, 2012)
(3aj GddZI GdYQHjI, GdHdGZI aj GdMOjK GdfHhj(B.s
(3GdCUd CWQhMI OcJhQGg(B-(3LGeYI Yjf TeS, cdjI GdBOGH(B.s
Keywords: (3GdMOjKs -- (3HdGZIs